Innovation and microenterprises growth in Ethiopia - Mulu Gebreeyesus (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper addresses two prominent issues on the development of small enterprises in Africa. Which factors inhibit or foster innovation activities in small enterprises? Do innovators create more jobs? We use a large set of microenterprises survey data from Ethiopia that comprise 1000 observations with ten and fewer workers. The analysis shows that firms larger in size and in manufacturing are more likely to engage in innovative activities. Among the human capital variables vocational training is found to have a strong effect on the innovation activity. However, firms owned by female and old entrepreneurs are less likely to get involved in innovation. In an extended model of firm growth determinants that includes innovation indicators we found strong evidence that innovators grow faster than non-innovators. Firm growth is also affected by other factors such as the firm's initial size, age, access to finance, sector, and owner character. Our estimation results provide supporting evidence to the stylized fact that the smaller, younger, and less capital constrained firms grow faster than their counterparts. Firms in manufacturing also grow faster than other sectors.
Keywords: L25; L26; O31; O55; 330; micro and small enterprises; firm growth; innovation; developing countries; Ethiopia; Klein- und Mittelunternehmen; Innovationsmanagement; Unternehmenswachstum; Äthiopien